Arhitektura in komunikacija - Hudnik, Špela (Urbani izziv, 2003)
The article presents effects of technology, science and capital strategies on changes in traditional forms and definitions of space, architecture and bodies. It confronts us with new processes of thinking and living that are constantly being transformed into new dynamic time and spatial contexts. Spaceis becoming the information filter, communication network. A cross-section of three landscapes: landscape of megastructures, nomadic landscapes and psychedelic landscapes, theory contributes to understanding of media and space-age technology, information technology and electronical language. It offers designs of various megastructures, media surfaces and envelopes of contemporary information society: the anthropological module, hyper- and infra-bodies, bio-electronical bodies and population genetics bodies. It presents the architecture of communication.
Keywords: architecture; arhitektura; communication; komuniciranje; mobilnost; navidezna resničnost; prostor; teorija arhitekture; vizualne komunikacije